K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 1 2022

\(2-\frac{1}{2}-\frac{5}{2}\)

\(=\)\(\frac{2}{2}-\frac{5}{2}\)

\(=\)\(1-\frac{5}{2}\)

\(=\)\(\frac{-3}{2}\)

a: \(=\dfrac{5}{\dfrac{2}{5}}\cdot\dfrac{4}{\dfrac{2}{7}}+\dfrac{5}{\dfrac{5}{7}}\cdot\dfrac{5}{\dfrac{2}{5}}\)

\(=5\cdot\dfrac{5}{2}\cdot4\cdot\dfrac{7}{2}+5\cdot\dfrac{5}{2}\cdot5\cdot\dfrac{7}{5}\)

\(=\dfrac{25}{2}\left(14+7\right)=\dfrac{25}{2}\cdot21=\dfrac{525}{2}\)

b: \(=\dfrac{3}{4}-2+\dfrac{1}{2}\cdot\dfrac{12}{5}-\dfrac{1}{4}\)

\(=\dfrac{6}{5}-2+\dfrac{1}{2}=-\dfrac{3}{10}\)

5 tháng 4 2018

Bài 1: Tính

1/ \(\dfrac{-2}{-5}-\left(\dfrac{-4}{3}\right)\)

\(=\dfrac{2}{5}-\left(\dfrac{-4}{3}\right)\)

\(=\dfrac{6}{15}-\left(\dfrac{-20}{15}\right)\)

\(=\dfrac{6-\left(-20\right)}{15}\)

\(=\dfrac{26}{15}\)

2/ \(\left(\dfrac{-2}{4}-\dfrac{1}{2}\right):\dfrac{2}{3}\)

\(=\left(\dfrac{-2}{4}-\dfrac{2}{4}\right):\dfrac{2}{3}\)

\(=-1:\dfrac{2}{3}\)

\(=-1.\dfrac{3}{2}\)

\(=\dfrac{-3}{2}\)

3/ \(\dfrac{5}{12}.\dfrac{17}{11}-\dfrac{5}{12}.\dfrac{7}{11}+\dfrac{5}{12}.\dfrac{1}{11}\)

\(=\dfrac{5}{12}.\left(\dfrac{17}{11}-\dfrac{7}{11}+\dfrac{1}{11}\right)\)

\(=\dfrac{5}{12}.\left(\dfrac{17-7+1}{11}\right)\)

\(=\dfrac{5}{12}.1\)

\(=\dfrac{5}{12}\)

10 tháng 5 2020

:D

10 tháng 5 2020

a, \(\frac{3}{5}+\frac{-4}{15}=\frac{9}{15}-\frac{4}{15}=\frac{5}{15}=\frac{1}{3}\)

b, \(\frac{-1}{3}+\frac{2}{5}+\frac{2}{15}=\frac{-5}{15}+\frac{6}{15}+\frac{2}{15}=\frac{3}{15}=\frac{1}{5}\)

c, \(\frac{-3}{5}+\frac{7}{21}+\frac{-4}{5}+\frac{7}{5}=\frac{-3}{5}+\frac{1}{3}+\frac{-4}{5}+\frac{7}{5}=\left(\frac{-3}{5}+\frac{-4}{5}+\frac{7}{5}\right)+\frac{1}{3}=\frac{1}{3}\)

d, \(\frac{2}{7}+\frac{1}{9}+\frac{3}{7}+\frac{5}{9}+\frac{-5}{6}=\left(\frac{2}{7}+\frac{3}{7}\right)+\left(\frac{1}{9}+\frac{5}{9}\right)+\frac{-5}{6}=\frac{5}{7}+\frac{6}{9}+\frac{-5}{6}=\frac{90}{126}+\frac{84}{126}+\frac{-105}{126}=\frac{69}{126}=\frac{23}{42}\)

e, \(\frac{-5}{7}+\frac{3}{4}+\frac{-1}{5}+\frac{-2}{7}+\frac{1}{4}=\left(\frac{-5}{7}+\frac{-2}{7}\right)+\left(\frac{3}{4}+\frac{1}{4}\right)+\frac{-1}{5}=\left(-1\right)+1+\frac{-1}{5}=\frac{-1}{5}\)

f, \(\frac{-3}{31}+\frac{-6}{17}+\frac{1}{25}+\frac{-28}{31}+\frac{-1}{17}+\frac{-1}{5}=\left(\frac{-3}{31}+\frac{-28}{31}\right)+\left(\frac{-6}{17}+\frac{-1}{17}\right)+\left(\frac{1}{25}+\frac{-1}{5}\right)=\left(-1\right)+\frac{-7}{17}+\frac{-4}{25}=\frac{-425}{425}+\frac{-175}{425}+\frac{-68}{425}=\frac{-668}{425}\)

Chúc bn học tốt

26 tháng 3 2021

i don'n know

18 tháng 2 2021

Abcfsgsgsgsgsggggggghyhjgfhnhgjfgefhefrgjhfgjhergfyebfqybrfjyebrfyerbfjqyrfgjyerqfyearfyaberjybqrfjhwqdicuvdaciuvicvdcu

18 tháng 2 2021

B=0,5274220522